Environmental advocacy model for Indonesia: lessons from Greta Thunberg's speeches in 2018-2022 - Novrel Esa Yubel; Nur Azizah (Jurnal Studi Komunikasi, 2024)
This article aims to analyse new advocacy model pioneered by young activist Greta Thunberg and its possible applications for Indonesia. Margareth E. Keck and Kathryn Sikkink's theoretical approaches is used in this study to include advocacy strategies incorporating information politics, symbolic politics, leverage politics, and accountability politics. The study uses a qualitative method, specifically utilising a literature review approach. Data visualisation and analysis were conducted using the Critical Discourse Analysis (CDA) and NVivo 12 software. Findings of this study show that Greta's new advocacy model effectively grabs the attention of young people and encourages them to take part in advocacy initiatives. It also highlights the need of environmental ethics as the foundation for advocacy initiatives. Indonesian teenagers lack knowledge to be pioneers because they do not grasp environmental ethics, which is crucial for environmental campaign. This article offers a new approach to the environmental movement in Indonesia, based on environmental ethics being led by young people.